Beyond Compare: Comparative Method after the Transnational Turn. - Seigel, Micol (Radical History Review)
Attributes the transnational approaches to history to anti- and postcolonial scholarship and argues that this body of thought contains an implicit critique of comparative method. Definition of transnational history; Benefits of comparison; Role of "Crisis" editor W. E. B. Du Bois in the comparison regarding racial equity between the U.S. and Brazil; Information on the black movements in the U.S. and Brazil.